Nurture, Worship and Religious Integrity in Church Schools - Steed, Mark S. (Journal of education & Christian belief, 1998)
THE AIM OF of this article is to discuss the parameters of what is and what is not legitimate practice in the context of Christian worship in Church schools. This paper claims that the notion of religious integrity lies at the heart of the issue and argues that Church schools have a responsibility not to violate the religious integrity of their pupils. Hence there must be a demarcation between those Christians who are participating in the act of worship and those non-Christians who are not.